1998
DOI: 10.1136/gut.43.4.571
|View full text |Cite
|
Sign up to set email alerts
|

A requiem for the cholecystokinin provocation test?

Abstract: Background-The cholecystokinin provocation test (CCKPT) has been claimed to predict a better symptomatic result after cholecystectomy in patients with acalculous biliary pain. Aims-To examine the predictive value of the CCKPT for symptom relief after cholecystectomy in both CCKPT positive and negative patients. Patients and methods-Fifty eight patients with acalculous biliary pain underwent CCKPT with serial ultrasound gall bladder volumetry. CCKPT positive patients were oVered cholecystectomy; negative patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…Ultrasonography of their GBs was taken to monitor initial volume, changes in shape, and volume as well as wall thickness at 5 or 15 minute intervals for 60 minutes. The test was only considered positive when the patients' usual 'gallbladder' pain was reproduced following CCK infusion (Smythe et al 1998). At point D, the sphincter of Oddi is closed, the patient is fasting, and the GB cavity volume and pressure are at their minimum levels.…”
Section: Cck Provocation Test and Problem Specificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrasonography of their GBs was taken to monitor initial volume, changes in shape, and volume as well as wall thickness at 5 or 15 minute intervals for 60 minutes. The test was only considered positive when the patients' usual 'gallbladder' pain was reproduced following CCK infusion (Smythe et al 1998). At point D, the sphincter of Oddi is closed, the patient is fasting, and the GB cavity volume and pressure are at their minimum levels.…”
Section: Cck Provocation Test and Problem Specificationmentioning
confidence: 99%
“…The pathogenesis of such disorders is not fully understood (Parkman et al 1999). Many researchers believe that it is related to mechanical responses trigged by smooth muscle contraction of the GB (Smythe et al 1998;Parkman et al 1999;Wegstapel et al 1999;Amaral et al 2001;Merg et al 2002). The mechanical behaviour of the human GB has been extensively studied, primarily using a linear membrane ellipsoid model (Liao et al 2004;Li et al 2008;Li et al 2011a;Li et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that only 50% of acalculous patients are free from pain symptoms after cholecystectomy. 50,51 A challenging task is to identify effectively these patients to reduce unnecessary surgery. Bile ejection fraction (EF), whereby the gallbladder-emptying contraction is measured by its volume change, has been used clinically, but it has been reported to be unreliable.…”
Section: Introductionmentioning
confidence: 99%